Plasma ADAMTS‐13 levels and the risk of myocardial infarction: an individual patient data meta‐analysis. (14th July 2015) - Maino, A.; Siegerink, B.; Lotta, L. A.; Crawley, J. T. B.; le Cessie, S.; Leebeek, F. W. G.; Lane, D. A.; Lowe, G. D. O.; Peyvandi, F.; Rosendaal, F. R.
Summary Background Low ADAMTS‐13 levels have been repeatedly associated with an increased risk of ischemic stroke, but results concerning the risk of myocardial infarction are inconclusive. Objectives To perform an individual patient data meta‐analysis from observational studies investigating the association between ADAMTS‐13 levels and myocardial infarction. Methods A one‐step meta‐analytic approach with random treatment effects was used to estimate pooled odds ratios (ORs) and corresponding 95% confidence intervals (CIs) adjusted for confounding. Analyses were based on dichotomous exposures, with the 5th and 1st percentiles of ADAMTS‐13 antigen levels as cut‐off values. Quartile analyses, with the highest quartile as a reference category, were used to assess a graded association between levels and risk ('dose' relationship). Additionally, we assessed the risk of the combined presence of low ADAMTS‐13 and high von Willebrand factor (VWF) levels. Results Five studies were included, yielding individual data on 1501 cases and 2258 controls (mean age of 49 years). Low ADAMTS‐13 levels were associated with myocardial infarction risk, with an OR of 1.89 (95% CI 1.15–3.12) for values below the 5th percentile versus above, and an OR of 4.21 (95% CI 1.73–10.21) for values below the 1st percentile versus above. Risk appeared to be restricted to these extreme levels, as there was no graded association between ADAMTS‐13 levels and myocardial infarction risk over quartiles. Finally, there was only a minor synergistic effect for the combination of low ADAMTS‐13 and high VWF levels. Conclusions Low ADAMTS‐13 levels are associated with an increased risk of myocardial infarction.